The Role of Corporate Social Responsibility in Reducing the Incidence of Business Crime: A Case Study in the Banking Sector - Ariza Qanita (Generate Digital Publishing, 2025)
Objective: This study aims to explore the role of CSR in reducing the incidence of business crime in the banking sector. Research Design & Methods: This research uses a systematic literature review method to analyze and classify literature sources such as books and journals related to the research topic, with stages including focus selection, article collection and reduction, compilation, and conclusion drawing. Findings: Through the implementation of CSR principles, companies not only strengthen a positive image in the eyes of stakeholders, but also create innovations that impact operational security and risk management. Community involvement in CSR initiatives enables banks to understand community needs and respond to concerns, and create relevant programs. Implications: Effective CSR implementation can increase customer trust, strengthen the company's reputation, and produce innovations that are more in line with the needs of society. Contribution: This study can contribute to the existing knowledge on the role of CSR in reducing business crime. By exploring the relationship between CSR and business crime in the banking sector